HOW MUSLIM YOUTH PSYCHOLOGICAL DEVELOPMENT CONTRIBUTES TO THEIR RELIGIOUS MATURITY - Tati Haryati; Munawar Rahmat (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This research aims to investigate the psychological development of Muslim youth and how it may contribute to the development of their religious maturity. A qualitative inquity, the study reviews relevant books and journal articles on psychological development and religious maturity. Data were then analyzed by ideas of leading Muslim scholars. Findings suggest that the psychological development of Muslim youth determine their religious maturity. As part of their development, youth experience different stages of psychological development including identity search as well trial and error in search of their identity. These phases lead to different stages of religious maturity among young people such as total belief in something, belief with awareness, belief with doubt, disbelief at all. This maturity is influenced by such development factors as personality, psychological condition, family and institutional environment, and social condition. Due to good psychological development, most Muslim youth experience good religious maturity as they become moderate followers of Islam. The study also suggests some recommendations how to provide Muslim youth with proper psychological development so that they become religious and moderate followers of Islam.